1979
DOI: 10.1177/000331977903000704
|View full text |Cite
|
Sign up to set email alerts
|

Specific Calcium Antagonists in the Treatment of Peripheral Vascular Disease

Abstract: The antivasoconstrictor activity of the drugs cinnarizine and flunarizine is considered in relation to their inhibitory action on calcium ion flux mechanisms. Their clinical efficacy in peripheral vascular disease is reviewed, and the possible mode of action of the two drugs is discussed in relation to their described pharmacologic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The decrease in regional blood flow during an attack of migraine is most probably due to a vasoconstriction [42][43][44][45]. It has been suggested that blood viscosity might play a role in the functional vascular diseases [46][47][48][49]. A significant change in viscosity measured before, during or after the cold test, in patients with vasospastic syndrome has never been observed [50].…”
Section: Etiology and Pathogenesis Of Vascular Spasmmentioning
confidence: 99%
“…The decrease in regional blood flow during an attack of migraine is most probably due to a vasoconstriction [42][43][44][45]. It has been suggested that blood viscosity might play a role in the functional vascular diseases [46][47][48][49]. A significant change in viscosity measured before, during or after the cold test, in patients with vasospastic syndrome has never been observed [50].…”
Section: Etiology and Pathogenesis Of Vascular Spasmmentioning
confidence: 99%
“…Flunarizine [(E)-l-bis(4-fluorophenyl)methyl-4-(3-phenyl-2-propenyl)-piperazine dihydrochloride], a selective calcium entry blocker [55,16,57], causes selective inhibition of SMC contractions [54] and of intracellular Ca 2+ deposition [8].…”
Section: The Drugmentioning
confidence: 99%
“…It acts as a peripheral labyrinth sedative, probably by blocking the calcium-influx from the endolymph to the vestibular sensory cells (12Y14) and by improving blood perfusion and metabolic activity in the vestibular nuclei (15). Cinnarizine is used in the dose range of 15 to 30 mg for the treatment of motion sickness, and it has been reported to be effective in the prevention of seasickness (14,16,17).…”
Section: Cinnarizine (20 Mg) and Dimenhydrinate (40 Mg)mentioning
confidence: 99%